(untitled) (Polish Yearbook of International Law, 2025)
The article aims to explore the enforcement of the International Covenant on Economic, Social and Cultural Rights (ICESCR) by administrative courts in Poland and Czechia. The concluding observations of the Committee on Economic, Social and Cultural Rights have suggested significant differences between the two countries in this regard for many years. However, the exact reasons underlying this discrepancy remained unclear. The paper provides comprehensive insight into this legal phenomenon. Firstly, the author reconstructs the obligations relating to the eco nomic, social and cultural (ESC) rights imposed on administrative courts. Secondly, the results of a large-scale review of the domestic rulings are presented. Based on the quantitative and qualitative analysis of the existing case law, it is revealed that the Polish and Czech courts share significant similarities in enforcing ESC rights. The study indicates that comparable shortcomings in terms of judicial enforcement of the Covenant are inherent in both jurisdictions. Thirdly, the author points to the existing methods available for the administrative courts that can still be used to strengthen the protection of the rights recognised in the ICESCR.